Implementasi Fungsi Manajemen di Lingkungan Dinas Tanaman Pangan,Hortikultura, dan Perkebunan Kabupaten Malang - Frida Lusiana Putri; Siti Mualifatur Rizqon Khasanah; Ismi Iftikad (Pusat Riset dan Inovasi Nasional, 2024)
Issues (GAP): The author focuses on understanding the extent to which these functions are implemented and how they impact on organizational performance in the Food Plant, Horticulture, and Farming Services of Malang District. Objective: This study aims to analyze the implementation of the management functions that exist in the agency, as well as to identify any factors that are impeding the application of such functions. Methods: This research uses descriptive qualitative methods, observations, and interviews with related stakehoslders. Research results: DTPHP has implemented a fairly good management function, but some officers need to be further enhanced in execution, the head of the division performs more control over the work, in order to reduce errors and deviations in tasks.These findings could provide insights for service management to improve operational efficiency, organizational performance, and overall public service.